Towards efficient, ecological assessment of interaction: A scoping review of co‐constructed communication. - Carragher, Marcella; Mok, Zaneta; Steel, Gillian; Conroy, Paul; Pettigrove, Kathryn; Rose, Miranda L.; Togher, Leanne (International Journal of Language & Communication Disorders (John Wiley & Sons, Inc.), 2024)
Background: The complexity of communication presents challenges for clinical assessment, outcome measurement and intervention for people with acquired brain injury. For the purposes of assessment or treatment, this complexity is usually managed by isolating specific linguistic functions or speech acts from the interactional context. Separating linguistic functions from their interactional context can lead to discourse being viewed as a static entity comprised of discrete features, rather than as a dynamic process of co‐constructing meaning. The ecological validity of discourse assessments which rely on the deconstruction of linguistic functions is unclear. Previous studies have reported assessment tasks that preserve some of the dialogic features of communication, but as yet, these tasks have not been identified as a distinct genre of assessment. We suggest the term 'co‐constructed communication' to describe tasks which are specifically designed to capture the dynamic, jointly produced nature of communication within a replicable assessment task. Aims: To identify and summarize how co‐constructed communication has been assessed with individuals with non‐progressive acquired communication disability regarding task design, measures and psychometric robustness. Methods: A scoping review methodology was used to identity relevant studies. Systematic database searches were conducted on studies published before July 2021. Studies in the yield were assessed against eligibility criteria, with 37 studies identified as eligible for inclusion. Main contribution: This is the first time that co‐constructed communication has been defined as a genre of discourse assessment for stroke and traumatic brain injury populations. Co‐constructed communication has been assessed for 144 individuals with aphasia and 111 with cognitive–communication disability. Five categories of co‐constructed communication tasks were identified, ranging in complexity. Variability exists in how these assessment tasks are labelled and measured. Assessment measures require further psychometric profiling, specifically regarding test–retest reliability and validity. Conclusions: Co‐constructed communication is a discourse genre which offers researchers and clinicians a replicable method to assess language and communication in an experimentally rigorous way, within an ecologically valid context, bridging the gap between experimental and ecological assessment approaches. What this paper adds: What is already known on this subject: Standardized assessments of language skills and monologue offer reliable, replicable ways to measure language. However, isolating language from an interactional context fundamentally changes the behaviour under study. This raises questions about the ecological validity of the measures we routinely use to determine diagnoses, guide treatment planning and measure the success of treatment. What this study adds to the existing knowledge: This review highlights studies that conceptualize, and often quantify, interaction by combining experimental rigour and aspects of everyday dialogue. This is the first time this genre of discourse assessment has been identified. We propose the term 'co‐constructed communication' to describe this genre and provide an operational definition for the term. What are the practical and clinical implications of this study?: Co‐constructed communication assessment tasks require refinement, particularly regarding aspects of psychometric robustness. In the future, these tasks offer pragmatic, meaningful ways to capture the effect and impact of aphasia and cognitive–communication disability within interaction.